The effectiveness of education intervention program for improving knowledge, attitude and practice related to hepatitis-B infection among non-medical and non-veterinary undergraduate university student in northern Nigeria, a randomized control community trial - Anka, Yakubu Hussaini; Rampal, Lekhraj; Ibrahim, Normala; Mohd Sidik, Sherina; Iliyasu, Zubairu (International Organization of Scientific Research, 2016)
Background: The endemicity of Hepatitis B virus (HBV) infection is leveling off in sub-Saharan Africa; it remains at an unacceptable high level (≥8%, to <2%) with global prevalence of 3·61%. The present study assessed the effectiveness of a peer-led HBV prevention education intervention in Usman Danfodiyo University Sokoto, Nigerian on youth’s HBV-related knowledge,attitude,and practices. Methods: In a peer-led single blind randomized controlled community trial conducted between April and December 2015. 390students were selected and randomized into the intervention and control arms, each arm with 195 respondents; five out of 12 faculties were selected using multi-staged random sampling. Four surveys were conducted(baseline, immediately, three and six months using self-administered questionnaire.Analysis of data were conducted using SPSS version 22. Results: The overall response rate during the four survey were 100%, 99.4%, 98.9% and 98.4%for intervention group and 100%, 100%, 99.4%,and 98.9% for the control arm respectively. Hepatitis B- related knowledge, attitude,and practices of the respondents were statistically significant between the intervention and the control arms at immediately, three and six month’s follow-up assessment with no statistical significant difference at baseline assessment (knowledge 14.3%, 66.95%, & 62.7%, HBV-related attitude 23.56%,40.68%, & 46.12% and HBV-related preventive practices 26.14%, 6.53%,& 11.9%). Conclusions: The present study has shown an evident for its effectiveness on HBV-related knowledge, attitude and preventive practice among the undergraduate non-medical and non-veterinary university students of Usman Danfodiyo University Sokoto Nigeria.